2009
DOI: 10.1186/1471-2105-10-202
|View full text |Cite
|
Sign up to set email alerts
|

NLStradamus: a simple Hidden Markov Model for nuclear localization signal prediction

Abstract: Background: Nuclear localization signals (NLSs) are stretches of residues within a protein that are important for the regulated nuclear import of the protein. Of the many import pathways that exist in yeast, the best characterized is termed the 'classical' NLS pathway. The classical NLS contains specific patterns of basic residues and computational methods have been designed to predict the location of these motifs on proteins. The consensus sequences, or patterns, for the other import pathways are less well-un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
433
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 587 publications
(444 citation statements)
references
References 26 publications
10
433
1
Order By: Relevance
“…In short, amino acid sequences for those proteins identified by MS were extracted from the SOL genomics protein database v. ITAG2.4 (Tomato Genome, 2012). This data set was subjected to predictnls (default settings) (Cokol et al ., 2000) and nlstradamus (two‐state model; posterior threshold 0.6) (Nguyen Ba et al ., 2009) to identify proteins with nuclear localization signals, and the Nucleolar Localization Sequence Detector ( nod ) (default settings) (Scott et al ., 2010, 2011) to identify proteins with nucleolar localization signals. Additionally, we used wolf psort (plant) (Horton et al ., 2007) and filtered all proteins marked as nuclear.…”
Section: Methodsmentioning
confidence: 99%
“…In short, amino acid sequences for those proteins identified by MS were extracted from the SOL genomics protein database v. ITAG2.4 (Tomato Genome, 2012). This data set was subjected to predictnls (default settings) (Cokol et al ., 2000) and nlstradamus (two‐state model; posterior threshold 0.6) (Nguyen Ba et al ., 2009) to identify proteins with nuclear localization signals, and the Nucleolar Localization Sequence Detector ( nod ) (default settings) (Scott et al ., 2010, 2011) to identify proteins with nucleolar localization signals. Additionally, we used wolf psort (plant) (Horton et al ., 2007) and filtered all proteins marked as nuclear.…”
Section: Methodsmentioning
confidence: 99%
“…The SAUR36 protein contains a nuclear localization signal, 59-RRRS-62 (Supplemental Fig. S1), predicted by the NLStradamus program (Nguyen Ba et al, 2009). A GFP fusion protein confirms that the SAUR36 protein is targeted to the nucleus (Narsai et al, 2011).…”
Section: Auxin May Promote Leaf Senescence In Arabidopsismentioning
confidence: 96%
“…Subcellular localization of proteins was performed using MultiLoc2 (Blum et al, 2009), and nucleus-localizing signals were identified using NLStradamus (Nguyen Ba et al, 2009). Protein secondary structures were predicted using PSIPRED (Bryson et al, 2005).…”
Section: Other Bioinformatics Tools Usedmentioning
confidence: 99%